Analysis and theoretical modeling of the 18O enriched carbon dioxide spectrum by CRDS near 1.74 µm. (September 2018) - Karlovets, E.V.; Čermák, P.; Mondelain, D.; Kassi, S.; Campargue, A.; Tashkun, S.A.; Perevalov, V.I.
Highlights: High sensitivity CRDS of CO2 enriched in 18 O in the 1.74 µm transparency window Very weak lines with intensity value as low as 10 −30 cm/molecule are detected. More than 3200 transitions assigned to 60 bands of nine isotopologues. Validation tests of the most recent spectroscopic databases: CDSD, HITRAN, NASA Ames. New sets of Δ P = 8 and 9 effective dipole moment parameters for several isotopologues. Abstract: The very weak absorption spectrum of the minor isotopologues of carbon dioxide near 1.74 µm (5702–5879 cm −1 ) is studied by high sensitivity cavity ring down spectroscopy (CRDS) with an 18 O enriched sample. The investigated spectral region corresponds to a transparency window of very weak opacity which is of particular interest for Venus. Very weak lines with intensity value as low as 10 −30 cm/molecule at 296 K are measured. On the basis of the predictions of the effective Hamiltonian models, 3202 lines of nine carbon dioxide isotopologues - 12 C 16 O2, 16 O 12 C 18 O, 16 O 12 C 17 O, 16 O 13 C 18 O, 16 O 13 C 17 O, 17 O 12 C 18 O, 17 O 13 C 18 O, 12 C 18 O2 and 13 C 18 O2 - were rovibrationnally assigned to 59 bands, 44 of which were observed for the first time. The accurate spectroscopic parameters of 53 bands are determined from standard band-by-band analysis (typical rms deviations of the line positions are 8 × 10 −4 cm −1 ). Three bands are found to be strongly perturbed by resonance first order Coriolis interaction. The new measured line intensities allowed determining or improving the Δ P = 8 sets of the effective dipole moment (EDM) parameters for five non-symmetrical isotopologues - 16 O 12 C 18 O, 16 O 12 C 17 O, 16 O 13 C 18 O, 16 O 13 C 17 O and 17 O 12 C 18 O - and Δ P = 9 sets for the 16 O 12 C 18 O and 12 C 18 O2 isotopologues ( P = 2V1 + V2 + 3V3 is the polyad number, Vi being the vibrational quantum numbers). The set of EDM parameters available for eleven isotopologues is used to discuss their isotopic dependence. These newly observed bands provide critical validation tests for the most recent spectroscopic databases. The comparison to the Carbon Dioxide Spectroscopic Databank (CDSD-296), HITRAN2016 database and ab initio Ames line list is presented. Deficiency is evidenced for the weak 41104–00001 band of 16 O 12 C 18 O in the HITRAN2016 list and identified as due to inaccurate CDSD intensities which were preferred to ab initio intensities.